IL-4 Deficiency Decreases Mortality but Increases Severity of Arthritis in Experimental Group B Streptococcus Infection - Luciana Tissi; Francesco Bistoni; Manuela Puliti (Mediators of Inflammation)
IL-4 is an anti-inflammatory cytokine that inhibits the onset and severity in different experimental arthritis models. Group B streptococci (GBS) have been recognized as an ever-growing cause of serious invasive infections in nonpregnant adults. Septic arthritis is a clinical manifestation of GBS infection. To investigate the role of IL-4 in experimental GBS infection, IL-4 deficient or competent mice were inoculated with 1×107 GBS/mouse. Mortality, appearance of arthritis, GBS growth in the organs, and local and systemic cytokine and chemokine production were examined. IL-4–/– mice showed lower mortality rates but increased severity of arthritis and exhibited a lower microbial load in blood, kidneys, and joints than wt mice. Increased local levels of IL-1 β, IL-6, TNF-α, MIP-1α, and MIP-2 accompanied the more severe arthritis in IL-4–/– mice. Our results suggest a detrimental role of IL-4 in GBS sepsis, whereas it plays a beneficial effect on GBS-induced arthritis.